O impacto das práticas do gerenciamento de falhas e erros na satisfação, engajamento e aprendizagem do trabalhador - Kussano, Walter Shuiti (2020)
Organizations are made up of people and regardless of the company's business segment, where human beings are active, they are invariably responsible for failures that cause consequences such as: defective products, rework, accidents and customer dissatisfaction. One way to take advantage of these occurrences as opportunities for improvement is through the implementation of the culture of failure and error management, the main objective of this research: assessing the impact of the culture of failure and error management, on individual learning, satisfaction and employee engagement through organizational practices: help behavior from coworkers, open management and employee empowerment. Data collection was carried out at the beginning of 2020 in a national industry, which was committed to quality and respect for the individual, with 128 valid questionnaires being collected. Data analysis was carried out through the modeling of structural equations, eight of the thirteen tested hypotheses being confirmed, whose results that can be highlighted are that the culture of failure and error management positively influences social support, empowerment and open management . From the results obtained, it was evidenced that the variables open management and social support from colleagues positively influence job satisfaction. The variable job satisfaction influences the engagement construct and it was also identified that the variables engagement and job satisfaction influence the individual's learning in the workplace. The results confirmed that empowerment does not influence: job satisfaction, engagement and individual learning in the workplace. As well, the variables: open management and social support do not influence engagement. A positive point to note is that 20% or more of the variance of endogenous variables was explained by the proposed model. In view of these results, it is possible to identify points of improvement or attention in the organization that is the focus of the research, with the possibility of building an action plan focused on personnel development, in addition, the scales validated for the Brazilian context can be used in future research or by companies for diagnostic and management purposes.